Referral practices of recent graduate and experienced physiotherapists working in Australian primary care for people with musculoskeletal conditions. (April 2023) - Macpherson, S.; Rebbeck, T.R.; Coates, S.; Evans, K.
Abstract: Background: People with musculoskeletal conditions often seek care from physiotherapists. Some, particularly those at risk of poor outcomes, may benefit from referral to physiotherapists with expertise in managing musculoskeletal conditions and/or multidisciplinary care. Understanding referral practices of physiotherapists, and how experience influences those practices, may assist in implementing optimal care pathways in primary care. Aims: Explore (i) current referral practices of recent graduate and experienced physiotherapists who manage musculoskeletal conditions; (ii) opinions about referral to specialist physiotherapists for people at risk of poor outcomes. Methods: This qualitative study consisted of 23 semi-structured interviews with recent graduate (n = 9) and experienced physiotherapists (n = 14) working in primary care. Perspectives of participants' current referral practices (to whom, when and why they are referred) and referral to specialist physiotherapists were sought. Interviews were recorded and transcribed verbatim prior to analysis. Results: Referral practices for both groups were influenced by specific diagnoses, complexity of presentations, confidence, self-awareness, the clinical environment and system-related factors. Experienced physiotherapists were more confident and specific in their referrals and had established trusted networks compared with new graduates. Early referral to specialist physiotherapists was more likely when therapists were co-located. Barriers to early referral were lack of awareness, health system factors and impact on the patient (e.g., financial, time, continuity of care). Conclusion: Understanding factors influencing referral decisions may improve both intra- and interprofessional care for people with musculoskeletal conditions. Referral of people at risk of poor outcomes to specialist physiotherapists may be improved by greater intraprofessional awareness and clarity of roles. Highlights: Patient, clinician and system factors affect physiotherapists' referral practices. Less experienced physiotherapists are more likely to refer to colleagues 'in-house'. Understanding specialist physiotherapists' scope may facilitate collaborative care.